Pengaruh Pembelajaran PKn Berbasis Multikultural terhadap Peningkatan Civic Competencies Siswa Sekolah Dasar dalam Kerangka Profil Pelajar Pancasila - Titin Sarwendah; Fikriana Fikriana; Ismatul Izza; Agil Kusuma; Zita Azaria; Aqgistya Shayra Junaidi (Peneliti.net, 2026)
This study aims to analyze the effect of multicultural-based Citizenship Education (PKn) learning on improving the civic competencies of elementary school students within the framework of the Pancasila Student Profile. The study used a quantitative approach with a quasi-experimental method through a one-group pretest-posttest design. The subjects were 27 fifth-grade students of SDN 7 Metro Utara. The research instruments included tests, observation sheets, and questionnaires. Data were analyzed using paired sample t-tests and N-gain tests. The results showed a significant increase in students' civic competencies, with the average score increasing from 75.37 to 83.30. The N-gain value of 0.32 is considered moderate. The t-test results showed a significance value of p < 0.001, indicating the effect of multicultural-based learning on improving students' civic competencies. These findings indicate that multicultural-based learning has the potential to support the strengthening of the Pancasila Student Profile in elementary schools.